Producción de cristales parasporales de Bacillus thuringiensis con potencial actividad anticancerígena (2021)
The species of the genus Bacillus are Gram positive bacteria and have a great capacity to form endospores. B. thuringiensis is one of the most studied species for its potential to produce cry proteins with cytotoxic activity against insects. Another group of proteins, parasporins that are formed as parasporal inclusion, show activity against cancer cells, but not against normal cells. 19 parasporins have been identified grouped into 6 families (PS1, PS2, PS3, PS4, PS5 and PS6), with sizes from 30 to 88 kDa, whose activity has been demonstrated on different lines of cancer in humans. Cervical cancer is a type of silent cancer related to the human papillomavirus (HPV), for which existing treatments are not entirely effective. Therefore, the purpose of this study was to obtain parasporal crystals from cell extracts of B. thuringiensis strains, which showed protein values of 8 to 115 μg / mL, a concentration that can be considered optimal for cytotoxicity tests. In addition, bands of proteins related to parasporins were identified by SDS-PAGE electrophoresis, with approximate sizes of 30, 33, 37, 70 and 88 kDa that can correspond to parasporins of all families. These results indicate that these proteins can be tested especially in cervical cancer cells as an alternative for an early and effective treatment.